2003
DOI: 10.1038/sj.onc.1206314
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of mammary carcinogenesis in a transgenic mouse model by α-difluoromethylornithine (DFMO) in the diet is associated with decreased cyclin D1 activity

Abstract: Mechanisms underlying the chemopreventive effect of difluoromethylornithine (DFMO) on the development of mammary cancer were investigated utilizing the whey acidic protein promoter-T antigen transgenic mouse model of breast cancer progression. Mice were exposed to four different doses of DFMO in the diet (3.5, 4.9, 7.0 and 10 g/kg diet). Tumor latency was increased in a dosedependent manner. DFMO at the highest dose significantly delayed tumor onset (131 days as compared to 109 days in control unexposed mice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…In most cells except for fibroblast cell lines, overexpression of cyclin D1 accelerates entry into the S phase, which is essential for the G 2 checkpoint, and thus is important for the modulation of radiation-induced cell death. The chemopreventive effect of DFMO on the proliferation of mammary cancer is known to be associated with decreased cyclin D1 activity (Li et al, 2003). DFMO-treated HT29 cells in our studies showed a reduction of cyclin D1 and an increase of HSP25, which is in accord with findings in other radiation-resistant cells.…”
Section: Discussionsupporting
confidence: 93%
“…In most cells except for fibroblast cell lines, overexpression of cyclin D1 accelerates entry into the S phase, which is essential for the G 2 checkpoint, and thus is important for the modulation of radiation-induced cell death. The chemopreventive effect of DFMO on the proliferation of mammary cancer is known to be associated with decreased cyclin D1 activity (Li et al, 2003). DFMO-treated HT29 cells in our studies showed a reduction of cyclin D1 and an increase of HSP25, which is in accord with findings in other radiation-resistant cells.…”
Section: Discussionsupporting
confidence: 93%
“…Odc has been shown to be important for tumor development in mouse models of lymphoma, skin, prostate, breast, and colon cancer, and most recently, neuroblastoma (10,11,(20)(21)(22)(23)(24). In the Eμ-Myc mouse, treatment with the suicide Odc enzyme inhibitor DFMO reduced rates of proliferation of B cells and delayed lymphomagenesis significantly (11).…”
Section: Resultsmentioning
confidence: 99%